Peningkatan Komunikasi Matematik Melalui Model Desain Pembelajaran Assure Berbasis Visual Basic - Desi Tri Utami (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Pratama Mulia Surakarta, 2018)
The purpose of this research was to find out the the effect of using ASSURE instructional design model based Visual Basic learning media to mathematical communication. This type of research is classroom action research. Methods of data collection of this study was by observation, test method, field note, and documentation. Data analysis techniques consist of data analysis process, data presentation, and data verification. The results of this study indicate an increase in students' mathematical communication. This is seen from the indicators: (1) the ability of students to express the symbols, notations, and mathematical equations completely and correctly before the action 31.25% and after the action 87.50%, (2) the ability of students in raising the problem / issue before action 18.75% and after action 68,75%, (3) student ability to respond problem / problem from other student before action 12,50% and after action 56,25%, and (4) ability of student to explain conclusion obtained before action 37.50% and after action 87.50%.